Oral Administration of Efavirenz Dysregulates the Tph2 Gene in Brain Serotonergic Areas and Alters Weight and Mood in Mice - Sandra Angélica Rojas-Osornio; Minerva Crespo-Ramírez; Vladimir Paredes-Cervantes; Antonio Mata-Marín; Ricardo Martínez-Lara; Miguel Pérez de la Mora; Emiliano Tesoro-Cruz (MDPI AG, 2024)
Most HIV-antiretroviral drugs have adverse effects. Efavirenz (EFV) is an example of a drug with neuropsychiatric effects, such as anxiety, depression, and suicidal thoughts, in people living with HIV (PLWH). The mechanisms by which EFV causes neuropsychiatric alterations in PLWH are complex, multifactorial, and not fully understood, although several studies in animals have reported changes in brain energy metabolism, alterations in monoamine turnover, GABA, and glutamate levels, and changes in 5-HT receptors. In this report, we studied the effects of EFV on the serotonergic system in healthy mice, specifically, whether EFV results in alterations in the levels of the tryptophan hydroxylase 2 (Tph2) gene in the brain. EFV (10 mg/kg) and distilled water (1.5 µL/kg) (control group) were orally administered to the mice for 36 days. At the end of the treatment, Tph2 expression levels in mouse brains were measured, and mood was evaluated by three trials: the forced swim test, elevated plus maze, and open field test. Our results revealed dysregulation of Tph2 expression in the brainstem, amygdala, and hypothalamus in the EFV group, and 5-HT levels increased in the amygdala in the EFV group. In the behavioral tests, mice given EFV exhibited a passive avoidance response in the forced swim test and anxiety-like behavior in the elevated plus maze, and they lost weight. Herein, for the first time, we showed that EFV triggered dysregulation of the Tph2 gene in the three serotonergic areas studied; and 5-HT levels increased in the amygdala using the ELISA method. However, further studies will be necessary to clarify the increase of 5-HT in the amygdala as well as understand the paradoxical decrease in body weight with the simultaneous increase in food consumption. It will also be necessary to measure 5-HT by other techniques different from ELISA, such as HPLC.